Nanoparticles containing intracellular proteins modulate neutrophil functional and phenotypic heterogeneity - Raudszus, Leonore; Bahreini, Farbod; Allan, Susanne; Kalies, Kai-Uwe; Caldwell, Charles C.; Kalies, Kathrin (Frontiers in Immunology, 2025)
Neutrophils are rapidly recruited to sites of infection, injury, or to immune complexes. Upon arrival, they initiate degranulation, release reactive oxygen species (ROS), and/or nuclear extracellular traps (NETs) to eliminate invading microorganisms, clear debris, or remove abnormal immunoglobulins. While these processes ideally trigger healing and a return to balance, overshooting neutrophil function can lead to life-threatening infections such as sepsis or persistent inflammation observed in various autoimmune diseases. However, recent evidence highlights a phenotypic and functional heterogeneity of neutrophils that extends well beyond their traditional - potentially harmful- role as first responders. For example, neutrophils regulate ongoing inflammation by modulating macrophage function through efferocytosis, T cell responses by antigen presentation and the release of cytokines. The factors that induce neutrophil differentiation into activating or regulatory phenotypes remain poorly defined. Here, we hypothesize that intracellular components that have been released into the extracellular space could contribute to the phenotypic heterogeneity of neutrophils. To find out, we used nanoparticles composed of intracellular proteins (cell-derived nanoparticles, CDNPs) and analyzed their effects on cultured murine bone marrow neutrophils (BMN). We observed that CDNPs activate BMN transiently with an increase in the expression of CD11b without triggering classical effector functions. Additionally, CDNPs induce the secretion of IL-10, shift PMA-induced cell death toward apoptosis, and increase the expression of CD80. Mechanistically, our findings indicate that 26% of BMNs ingest CDNPs. These BMNs preferentially express CD54+, fail to migrate toward CXCL12, exhibit diminished responses to LPS, and undergo apoptosis. These data identify CDNPs as biomaterials that modulate neutrophil behavior by fine-tuning the expression of CD11b and CD80.